2001
DOI: 10.1159/000051032
|View full text |Cite
|
Sign up to set email alerts
|

Flow in Elliptical Vessels Calculated for a Physiological Waveform

Abstract: Understanding the nature of pulsatile flow is an important issue in haemodynamics, especially the initiation and progression of vascular disease. The geometry of a non-circular vessel was idealised to an elliptical cross-section, and the dynamic properties of the flow were calculated for a physiological waveform. The Fourier harmonics for a common carotid waveform were determined, and the velocity profile and wall shear stress were calculated from the superposition of the individual contributions from each har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…In particular, by invoking separation of variables (in elliptical coordinates) we obtained a tridiagonal system of linear, ordinary differential equations and we obtained the sought solution by means of a Galerkin-type truncation. This method seem to theoretically corroborate the early attempts in [49] (in which proper references to the inverse problem are missing). Moreover, it represents an alternative to the numerical approach in [24], heavily based on a wise computation strategy of the Mathieu functions.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In particular, by invoking separation of variables (in elliptical coordinates) we obtained a tridiagonal system of linear, ordinary differential equations and we obtained the sought solution by means of a Galerkin-type truncation. This method seem to theoretically corroborate the early attempts in [49] (in which proper references to the inverse problem are missing). Moreover, it represents an alternative to the numerical approach in [24], heavily based on a wise computation strategy of the Mathieu functions.…”
Section: Discussionsupporting
confidence: 77%
“…Indeed, vessel ellipticity affects such a stress [26], which in turn has been identified as a key player in the onset and development of relevant pathologies likes atherosclerosis, even if several acquisitions needs to be consolidated (see e.g. [49,10]). Furthermore, still within the context of bio-fluid dynamics, many investigations are being carried out for elucidating the role of CSF dynamics within human spine, in relation to the onset and progression of relevant diseases like syringomyelia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the WSS vectors are not identical all around the wall, even from the CFD calculations. Higher values are found on the front and rear surfaces, i.e., at the ends of the minor axis (26). We believe that the model section is genuinely elliptical, as we have observed this effect on several occasions and with independent segmentation techniques.…”
Section: Discussionsupporting
confidence: 58%
“…5 and Table II) showed that slightly noncircular models of the cerebral aqueduct were not relevant, and called for fully elliptic cross sections geometries. Also, a Fourier mode decomposition of the flow rate during the cardiac cycle, similar to [22], is proposed in the next sections.…”
Section: A Aqueduct Reconstructionmentioning
confidence: 99%